2021
DOI: 10.1088/2515-7620/abed92
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in NO2 concentrations in Seoul, South Korea detected from space and ground-based monitors prior to and during the COVID-19 pandemic

Abstract: Nitrogen oxides detected in urban regions are primarily emitted by transportation methods and are crucial precursors for air pollutants and climate forcers such as ozone and fine particulate matter. We investigate the trends of nitrogen dioxide (NO2) obtained from a satellite instrument and surface monitors over the megacity, Seoul, South Korea, from 2005 to 2019. Both satellite Ozone Monitoring Instrument NO2 and surface in situ concentrations decreased by up to 30% between 2015 and 2019 while significant tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…There is a decreasing trend over the 2015-2019 period as previously reported by Seo et al (2021), more so in summer than in winter.…”
Section: Airkorea Data and Trends 2015-2019supporting
confidence: 75%
See 2 more Smart Citations
“…There is a decreasing trend over the 2015-2019 period as previously reported by Seo et al (2021), more so in summer than in winter.…”
Section: Airkorea Data and Trends 2015-2019supporting
confidence: 75%
“…Declining NO2 in the SMA can be attributed to policies to decrease vehicular NOx emissions (Kim and Lee, 2018). The weaker decline in winter is consistent with findings 160 from Seo et al (2021), who found that surface NO2 concentrations in the SMA in 2015-2019 declined by 5.3% a -1 during morning commute time for the ozone season, but only by 2.6% a -1 for the non-ozone season. The weaker response of NO2 to reduced NOx emissions in winter could be due to ozone titration by emitted NO, which would take place most systematically at night but also extend to daytime if the ozone supply is weak.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Gas‐phase precursors mainly emitted from fossil‐fuel combustion generate aqueous‐phase secondary aerosols with an aerodynamic diameter of less than 2.5 μm (PM 2.5 ) in the atmospheric boundary layer (Kumar et al., 2021; Wang, Ye, et al., 2021). Despite the decreased trend of anthropogenic precursors in eastern China since approximately 2006–2008 (Jia & Quaas, 2023; Lu et al., 2011), particularly during the COVID‐19 pandemic period from 2020, the occurrence of frequent severe hazes has persisted in eastern China and extended toward Korea (Cho et al., 2022; Seo et al., 2021; Shao et al., 2018; Wang, Wang, et al., 2021). This phenomenon is attributed to the heightened production of PM 2.5 through aqueous chemistry processes during transboundary transport (Cho et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be useful to investigate ozone trends in South Korea separately for spring and summer. There were large changes in atmospheric composition during the COVID-19 pandemic (Bauwens et al, 2020;Koo et al, 2020;Seo et al, 2021). The deviations caused by the pandemic from the long-term trends would provide a valuable perspective for planning of future environmental policy to improve ozone pollution.…”
Section: Introductionmentioning
confidence: 99%